Indian historiography in the United States since 1950 - Gélinas, Claude (Revista de Historia Social y de las Mentalidades, 2013)
In this article I am going to present some works that have marked Indian historiography in the United States since 1950. Of course, it is not an exhaustive review of the literature, since monographs and specialized articles in this field today include by thousands. Rather, we will limit ourselves to presenting a certain number of studies that are among the most representative of the different methodological, theoretical and ideological currents that have marked the sector, by the way, very dynamic of Indian history since 1950, a sector frequently called New Indian History
Keywords: Ethno-history; ethnohistorians; Euro-americans